Biology and Management of Cogongrass - Rick Williams; Patrick J. Minogue (EDIS)
FOR-191, a 3-page illustrated fact sheet by Rick Williams and Patrick J. Minogue, describes the biology and management strategies for this noxious weed native to warm regions of southeast Asia that can cause loss of productive forest areas, hinder forest activities and severely degrade wildlife habitat by replacing native plants. Includes references. Published by the UF School of Forest Resources and Conservation, May 2008.